Трагоцерины (Tragocerinae) Восточной Европы - Короткевич, Е.Л. (Вестник зоологии, 1980)
Based on the studies of new materials and the revision of old Neogenic Bovidae of
the Tragocerini tribe in the territory of Eastern Europe, different genera of these pecumar ruminants are differentiated.
Their adaptation peculiarities and phylogenetic interrelations are considered; groupings possibly worth distinguishing as individual subtribes
are suggested. A simultaneous habitation in the territory of Eastern Europe of several
Tragocerini genera belonging to different phylogenetic branches was due to their parallel
development, adaptation to various food, habitats, etc.